2018
DOI: 10.15171/jrip.2018.06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mindfulness-based cognitive therapy on quality of life and self-efficacy in dialysis patients

Abstract: Introduction: Amongst other problems, dialysis patients also present mental and psychological problems. Objectives: In this study, we investigated the effect of mindfulness-based cognitive therapy (MBCT) on quality of life and self-efficacy in hemodialysis patients. Patients and Methods: In a descriptive study, 50 hemodialysis patients undergoing dialysis in Hajar hospital were randomly selected and divided into two groups of experimental and control. The experimental group attended 2 to 2.5 hours treatment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…Having in mind that the reduction in pain is not the primary objective of mindfulness-based treatments, the results allow us to think that the improvement in pain variables may not be solely due to the decrease in intensity but due to the improvement of other cognitive processes, like self-efficacy. In fact, in our study we found significant differences in self-efficacy for the total scale, symptom management, and pain control but not in the physical functioning subscale, consistent with previous studies [ 50 , 52 ]. Something similar happens with regard to the quality-of-life scales, since only the mental quality of life subscale improves, but not the physical one, partially coinciding with previous results [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…Having in mind that the reduction in pain is not the primary objective of mindfulness-based treatments, the results allow us to think that the improvement in pain variables may not be solely due to the decrease in intensity but due to the improvement of other cognitive processes, like self-efficacy. In fact, in our study we found significant differences in self-efficacy for the total scale, symptom management, and pain control but not in the physical functioning subscale, consistent with previous studies [ 50 , 52 ]. Something similar happens with regard to the quality-of-life scales, since only the mental quality of life subscale improves, but not the physical one, partially coinciding with previous results [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…Of these, 6 studies were excluded mainly because they were abstracts published in conferences, full text in a language other than English, and other interventions in conjunction with mindfulness. As a result, 5 RCTs [36][37][38]44,45 and 1 crossover RCT 39 were included for data extraction and quality assessments. The included studies were published between the years 2014 to 2019.…”
Section: Results Study Selectionmentioning
confidence: 99%
“…Only two studies performed follow-up after the intervention, Gross et al ( 2017) 38 with a six-month follow-up and Nejad et al ( 2018) 44 with a one-month follow-up. Most studies excluded participants with suicidal ideation, psychotic disorder, expecting to receive a transplant within three months, and regularly practicing meditation [36][37][38]44,45 .…”
Section: Results Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations